1981
DOI: 10.1128/mcb.1.4.303
|View full text |Cite
|
Sign up to set email alerts
|

In vitro translation of the intermediate filament proteins desmin and vimentin.

Abstract: Polyadenylated ribonucleic acid (RNA) was isolated from chicken skeletal and smooth muscle and translated in a cell-free rabbit reticulocycle system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
15
0

Year Published

1981
1981
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 20 publications
3
15
0
Order By: Relevance
“…Although mature (7-to 8-day-old) myotubes showed increases in phosphorylation, myoblasts showed no changes in phosphorylation when exposed to either agonists or cAMP analogs. These data, in conjunction with our previous studies of cAMP-dependent phosphorylation of desmin and vimentin in vitro (18,19), suggest that the IF proteins desmin and vimentin are phosphorylated by the cAMP-dependent protein kinase in vivo and that changes in intracellular cAMP levels during differentiation may modulate IF protein phosphorylation and thereby regulate IF function.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Although mature (7-to 8-day-old) myotubes showed increases in phosphorylation, myoblasts showed no changes in phosphorylation when exposed to either agonists or cAMP analogs. These data, in conjunction with our previous studies of cAMP-dependent phosphorylation of desmin and vimentin in vitro (18,19), suggest that the IF proteins desmin and vimentin are phosphorylated by the cAMP-dependent protein kinase in vivo and that changes in intracellular cAMP levels during differentiation may modulate IF protein phosphorylation and thereby regulate IF function.…”
Section: Discussionsupporting
confidence: 68%
“…Two-dimensional tryptic mapping of '2PO4-labeled desmin and vimentin was performed essentially as described previously (19). Myotubes (8 days old; 106 cells per 100-mm plate) were labeled as described above for 4 h with 100 LCi of 32P04 per ml.…”
Section: Methodsmentioning
confidence: 99%
“…One-dimensional peptide mapping has indicated that thermin A and B are not identical polypeptides. This difference is further strengthened by the fact that both forms of thermin are translated in a reticulocyte cell-free system using poly(A)+mRNA obtained from chicken embryonic fibroblasts treated with so- (7) or from chicken smooth and skeletal muscle (14). In This argument is strengthened by the observation that, under these conditions, the 'normal level of methylation of thermin is not.inhibited.…”
mentioning
confidence: 66%
“…If other co-or post-translational modifications are involved, such modifications would have to be brought about in both the living Xenopus oocyte and the rabbit reticulocyte lysate (for specific acetylation and phosphorylation changes in both systems, see refs. [29][30][31][32]. Our experiments further show that proteins N1-N4 as synthesized in vitro are readily accumulated in nuclei not only ofthe same species but also ofanother, taxonomically distant, amphibian species.…”
mentioning
confidence: 56%
“…5i) Results of this study show that four of the most prominent karyophilic proteins (Ni-N4) of the Xenopus oocyte nucleus appear, on synthesis by translation in vitro, in the form of molecules indistinguishable from the specific polypeptides present in nuclei of living oocytes, as judged from two-dimensional gel electrophoresis and-in the case ofproteins Ni/N2-also from peptide maps and reaction with antibodies. In view of the high sensitivity of the gel electrophoretic procedure used, which allows the detection of single phosphorylation and acetylation differences in polypeptides (29,31), we conclude that these proteins are not synthesized in the form ofprecursor molecules considerably different, by size and charge, from the molecules present in the nucleus. Polypeptides Ni and N2 seem to be phosphorylated to the same degree both in vivo and in vitro.…”
mentioning
confidence: 90%